Differential forces within the proximal Patellar tendon as an explanation for the characteristic lesion of Patellar tendinopathy - Dillon, E. M.; Erasmus, P. J.; Müller, J. H.; Scheffer, C.; de Villiers, V. P. (The American Journal of Sports Medicine, 2008)
Patellar tendinopathy is a common condition affecting the posterior region of the proximal patellar tendon, but the reason for this typical location remains unclear.